Implants for osteosynthesis. Bone plates. Specification for holes and slots for use with screws of 4, 5 mm, 4, 2 mm, 4, 0 mm, 3, 9 mm, 3, 5 mm and 2, 9 mm nominal sizes Part 23.2, (15th May 1993) - British Standards Institution,
No abstract available